Identification of a novel RIG-I isoform and its truncating variant in Japanese eel, Anguilla japonica. Issue 94 (November 2019) - Huang, B.; Wang, Z.X.; Zhang, C.; Zhai, S.W.; Han, Y.S.; Huang, W.S.; Nie, P.
Abstract: Retinoic acid-inducible gene-I (RIG-I) is a cytoplasmic viral RNA sensor that triggers the production of type I interferons (IFNs) and proinflammatory cytokines during viral infection. RIG-I gene has been identified previously in Japanese eel, Anguilla japonica . In the present study, we have characterized a novel isoform of RIG-I (designated as AjRIG-Ib) and its truncated variant (AjRIG-Ibv). The AjRIG-Ib encodes 940 amino acids (aa) consisting of two N-terminal caspase activation and recruitment domains (CARDs), a DEX(D/H) box RNA helicase domain, and a C-terminal regulatory domain (CTD). The AjRIG-Ibv encodes a protein of 843 aa, that shares similar structural organization with AjRIG-Ib, but lacking CTD. The gene expression analyses showed that AjRIG-Ib and AjRIG-Ibv were detectable in all tissues/organs examined, and AjRIG-Ib was the predominant form. The mRNA level of AjRIG-Ibv was upregulated rapidly at 8 h after the Poly I:C injection, and the significant increase of AjRIG-Ib was observed at 16 and 24 h post-injection (hpi). Laser confocal microscopy showed that AjRIG-Ib and AjRIG-Ibv were both located in cytoplasm. In addition, the overexpression of AjRIG-Ib or AjRIG-Ibv led to the increased activity of IFN promoter in transient transfection assay. Taken together, our results indicated that AjRIG-Ib and AjRIG-Ibv may play cooperative or somewhat complementary roles in coordinating the antiviral response in fish. Highlights: A novel isoform of RIG-I and its truncated variant lacking the C-terminal domain were identified in Japanese eel. The two variants share similar sub-cellular localization and IFN promoter inducibility. The expression of truncated RIG-I variant increased rapidly upon Poly I:C stimulation. The two RIG-I variants may play cooperative or complementary roles in antiviral response.